Sources of low-frequency variability in observed Antarctic sea ice - Bonan, D. B.; Dörr, J.; Wills, R. C. J.; Thompson, A. F.; Årthun, M. (The Cryosphere, 2024)
Antarctic sea ice has exhibited significant variability over the satellite record, including a period of prolonged and gradual expansion, as well as a period of sudden decline. A number of mechanisms have been proposed to explain this variability, but how each mechanism manifests spatially and temporally remains poorly understood. Here, we use a statistical method called low-frequency component analysis to analyze the spatiotemporal structure of observed Antarctic sea ice concentration variability. The identified patterns reveal distinct modes of low-frequency sea ice variability. The leading mode, which accounts for the large-scale, gradual expansion of sea ice, is associated with the Interdecadal Pacific Oscillation and resembles the observed sea surface temperature trend pattern that climate models have trouble reproducing. The second mode is associated with the central Pacific El Niño–Southern Oscillation (ENSO) and the Southern Annular Mode and accounts for most of the sea ice variability in the Ross Sea. The third mode is associated with the eastern Pacific ENSO and Amundsen Sea Low and accounts for most of the pan-Antarctic sea ice variability and almost all of the sea ice variability in the Weddell Sea. The third mode is also related to periods of abrupt Antarctic sea ice decline that are associated with a weakening of the circumpolar westerlies, which favors surface warming through a shoaling of the ocean mixed layer and decreased northward Ekman heat transport. Broadly, these results suggest that climate model biases in long-term Antarctic sea ice and large-scale sea surface temperature trends are related to each other and that eastern Pacific ENSO variability is a key ingredient for abrupt Antarctic sea ice changes.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Glacial–interglacial Circumpolar Deep Water temperatures during the last 800 000 years: estimates from a synthesis of bottom water temperature reconstructions - Chandler, D. M.; Langebroek, Petra M. (Clim. Past, 2024)
Future climate and sea level projections depend sensitively on the response of the Antarctic Ice Sheet to ocean-driven melting and the resulting freshwater fluxes into the Southern Ocean. Circumpolar Deep Water (CDW) transport across the Antarctic continental shelf and into cavities beneath ice shelves is increasingly recognised as a crucial heat source for ice shelf melt. Quantifying past changes in the temperature of CDW is therefore of great benefit for modelling ice sheet response to past warm climates, for validating paleoclimate models, and for putting recent and projected changes in CDW temperature into context. Here we compile the available bottom water temperature reconstructions representative of CDW over the past 800 kyr. Estimated interglacial warming reached anomalies of +0.6 +/- 0.4 degrees C (MIS 11) and +0.5 +/- 0.5 degrees C (MIS 5) relative to present. Glacial cooling typically reached anomalies of ca. -1.5 to -2 degrees C, therefore maintaining positive thermal forcing for ice shelf melt even during glacials in the Amundsen Sea region of West Antarctica. Despite high variance amongst a small number of records and poor (4 kyr) temporal resolution, we find persistent and close relationships between our estimated CDW temperature and Southern Ocean sea surface temperature, Antarctic surface air temperature, and global deep-water temperature reconstructions at glacial-cycle timescales. Given the important role that CDW plays in connecting the world's three main ocean basins and in driving Antarctic Ice Sheet mass loss, additional temperature reconstructions targeting CDW are urgently needed to increase temporal and spatial resolution and to decrease uncertainty in past CDW temperatures - whether for use as a boundary condition, for model validation, or for understanding past oceanographic changes.
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

Observed water-mass characteristics and circulation off Prydz Bay, East Antarctica - Foppert, Annie; Bestley, Sophie; Shadwick, Elizabeth H.; Klocker, Andreas; Vives, Clara R.; Liniger, Guillaume; Westwood, Karen J. (Frontiers in Marine Science, 2024)
Circulation and water masses in the greater Prydz Bay region were surveyed in the austral summer 2021 (January-March) during the ‘Trends in Euphausiids off Mawson, Predators and Oceanography’ (TEMPO) experiment, and are described in this paper. The Southern Antarctic Circumpolar Current Front is found in the northern part of the survey area, generally near 63-64°S, whereas the Southern Boundary Front is located between 64 and 65.5°S. The westward flowing Antarctic Slope Front (ASF) is found in the southern part of the survey area near the continental slope on most transects. Highest concentrations of oxygen (> 300 µmol kg−1) are found in shelf waters at stations in Prydz Bay, south of 67°S along 75°E, whereas the lowest oxygen values are found in the Circumpolar Deep Water layer, with an average of roughly 215 µmol kg−1. North of the northern extension of the ASF, surface mixed layers are between 20 and 60 m deep. Mixed layers tend to deepen slightly in the northern part of the survey, generally increasing north of 64°S where the ocean has been ice-free the longest. We find evidence of upwelling of waters into the surface layers, based on temperature anomaly, particularly strong along 80°E. Enhanced variability of biogeochemical properties - nutrients, DIC, DO - in the AASW layer is driven by a combination of sea-ice and biological processes. Antarctic Bottom Water, defined as water with neutral density > 28.3 kg m-3, was sampled at all the offshore full-depth stations, with a colder/fresher variety along western transects and a warmer/saltier variety in the east. Newly formed Antarctic Bottom Water – the coldest, freshest, and most recently ventilated – is mostly found in the deep ocean along 65°E, in the base of the Daly Canyon.
Keywords: AABW; Sørishavet; klimatologi; oseanografi; vannmasser

An Assessment of Subseasonal Prediction Skill of the Antarctic Sea Ice Edge - Gao, Yuchun; Xiu, Yongwu; Nie, Yafei; Luo, Hao; Yang, Qinghua; Zampieri, Lorenzo; Lv, Xianqing; Uotila, Petteri (Journal of Geophysical Research: Oceans, 2024)
Abstract In this study, the subseasonal Antarctic sea ice edge prediction skill of the Copernicus Climate Change Service (C3S) and Subseasonal to Seasonal (S2S) projects was evaluated by a probabilistic metric, the spatial probability score (SPS). Both projects provide subseasonal to seasonal scale forecasts of multiple coupled dynamical systems. We found that predictions by individual dynamical systems remain skillful for up to 38 days (i.e., the ECMWF system). Regionally, dynamical systems are better at predicting the sea ice edge in the West Antarctic than in the East Antarctic. However, the seasonal variations of the prediction skill are partly system-dependent as some systems have a freezing-season bias, some had a melting-season bias, and some had a season-independent bias. Further analysis reveals that the model initialization is the crucial prerequisite for skillful subseasonal sea ice prediction. For those systems with the most realistic initialization, the model physics dictates the propagation of initialization errors and, consequently, the temporal length of predictive skill. Additionally, we found that the SPS-characterized prediction skill could be improved by increasing the ensemble size to gain a more realistic ensemble spread. Based on the C3S systems, we constructed a multi-model forecast from the above principles. This forecast consistently demonstrated a superior prediction skill compared to individual dynamical systems or statistical observation-based benchmarks. In summary, our results elucidate the most important factors (i.e., the model initialization and the model physics) affecting the currently available subseasonal Antarctic sea ice prediction systems and highlighting the opportunities to improve them significantly.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; sjøis

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi